2016
DOI: 10.5455/ja.20160711115722
|View full text |Cite
|
Sign up to set email alerts
|

Effect of honey on the body weight of glibenclamide treated alloxan induced diabetic rats.

Abstract: Aim/ Background: One of the classical features of diabetes mellitus is weight loss which may become excessive in some cases. This basically results from muscle wasting due to increased catabolism of proteins. The commonly used antidiabetic drug; glibenclamide may not effectively prevent the excessive weight loss experienced by some diabetics. This is the reason why some complain of even extreme weight loss while on medication. Thus addition of a natural product with the potential to prevent excessive weight lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Pasupuleti and coworkers documented that the fructose contained in honey improved hyperglycemia in experimental diabetic animals and diabetic patients [ 6 ]. Likewise, dietary fructose has been found to improve glycemic status by enhancing glucokinase activity and thereby catalyzing the conversion of glucose to glucose-6-phosphate and increasing hepatic glucose uptake (storage of glucose as glycogen by the liver tissue) [ 79 ]. For that, besides phenolic compounds and many other macro/microantioxidant nutrients, fructose-rich honey might be at least useful to enhance human physiological abilities and prevent several metabolic disorders, including diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Pasupuleti and coworkers documented that the fructose contained in honey improved hyperglycemia in experimental diabetic animals and diabetic patients [ 6 ]. Likewise, dietary fructose has been found to improve glycemic status by enhancing glucokinase activity and thereby catalyzing the conversion of glucose to glucose-6-phosphate and increasing hepatic glucose uptake (storage of glucose as glycogen by the liver tissue) [ 79 ]. For that, besides phenolic compounds and many other macro/microantioxidant nutrients, fructose-rich honey might be at least useful to enhance human physiological abilities and prevent several metabolic disorders, including diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its impact on the physical state and sensory characteristics of honey, the F/G ratio continues to be a crucial variable that condition or even restricts the use of honey in many critical physiological situations, such as glucose and lipid metabolic dysfunctions. Previous scientific data documented that fructose contained in honey decreased markedly the fasting blood glucose level in diabetic rat models and improve the lipid status of diabetes patients [56,57]. For that, in addition to antioxidant molecules and many other bio-valuable micro/macronutrients, fructose-rich honey might be at least useful to enhance human physiological abilities and prevents several metabolic disorders including dyslipidemia and diabetes.…”
Section: Physicochemical Analysis Of Honey and Bee Pollenmentioning
confidence: 99%
“…Therefore, there is renewed interest in health benefits of honey as well as believe of the efficacious, safer, relatively fewer side effects and reduction in its cost effectiveness treatment. So, we have extended our previous studies (15,16) to show the effect of long-term dietary honey on kidney function and lipid metabolism in normal and alloxan induced diabetic rats, for better understanding of the medicinal properties of Niger Delta honey.…”
Section: Introductionmentioning
confidence: 76%
“…Little is currently known about the potential medicinal beneficial effects of natural honey from the Niger Delta region of Nigeria. In our previous study, we reported that honey administered groups adopted in the study of the alloxan diabetic models gave positive results according to the parameters studied [15,16]. Therefore, there is renewed interest in health benefits of honey as well as believe of the efficacious, safer, relatively fewer side effects and reduction in its cost effectiveness treatment.…”
Section: Introductionmentioning
confidence: 99%